Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
A= ( 2x+3)(x-1) - (x+1)(2x-5) -2
= \(2x^2-2x+3x-3-\left(2x^2-5x+2x-5\right)-2\)
= \(2x^2-2x+3x-3-2x^2+5x-2x+5-2\)
= \(4x\)
B= \(\left(x-4\right)\left(x-2\right)-\left(3x+1\right)\left(\frac{1}{3}x-2\right)+2\frac{1}{3}x-10\)
= \(x^2-2x-4x+8-\left(x^2-6x+\frac{1}{3}x-2\right)+\frac{7}{3}x-10\)
= \(x^2-2x-4x+8-x^2+6x-\frac{1}{3}x+2+\frac{7}{3}x-10\)
= \(2x\)
Ta được: \(\frac{A}{B}=\frac{4x}{2x}=2\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(A=2x^2-2x+3x-3-\left(2x^2-5x+2x-5\right)-2\)
\(=2x^2+x-5-2x^2+3x+5=4x\)
\(B=x^2-6x+8-\left(x^2-6x+\dfrac{1}{3}x-2\right)+\dfrac{7}{3}x-10\)
\(=x^2-\dfrac{11}{3}x-2-x^2+6x-\dfrac{1}{3}x+2\)
\(=2x\)
Vậy: A=2B
![](https://rs.olm.vn/images/avt/0.png?1311)
b)\(B=\frac{x^2-3x+7}{x-3}=\frac{x\left(x-3\right)+7}{x-3}=x+\frac{7}{x-3}\)
\(\Rightarrow B\in Z\Leftrightarrow x+\frac{7}{x-3}\in Z\Leftrightarrow x\in Z,\frac{7}{x-3}\in Z\Leftrightarrow7⋮x-3\Leftrightarrow x-3\inƯ\left\{7\right\}\)
\(\Rightarrow x-3\in\left\{-1;-7;1;7\right\}\)
\(\Rightarrow x\in\left\{2;-4;4;10\right\}\)
c)\(C=\frac{x^2+1}{x-1}=\frac{x^2-1+2}{x-1}=\frac{\left(x-1\right)\left(x+1\right)+2}{x-1}=\left(x+1\right)+\frac{2}{x-1}\)
\(\Rightarrow C\in Z\Leftrightarrow\left(x+1\right)+\frac{2}{x-1}\in Z\Leftrightarrow x-1\in Z;\frac{2}{x-1}\in Z\)
\(\Leftrightarrow x\in Z;2⋮x-1\Rightarrow x-1\inƯ\left(2\right)\)
\(\Rightarrow x-1\in\left\{-1;-2;1;2\right\}\)
\(\Rightarrow x\in\left\{0;-1;2;3\right\}\)